Pfinzing, ein vergessener Kartograph - Gagel, Ernst (ERDKUNDE, 1957)
The purpose of the paper is to draw attention to an important German cartographer of the 16 th century, the Nuremberg senator Paul Pfiwyng (1554—1599). Pfin- Zing’s importance lies in the field of topographic (medium scale) maps and further in the fact that he developed the system of surveying by means of a compass traverse. He wrote about his experiences as a cartographer in a book which was published in 1598. In it he explains in German all the fields of practical cartography from the making of the necessary instruments and the surveying in the field, to the construction of the map on the drawing board.